Synergistic Rescue of Nonsense Mutant Tumor Suppressor p53 by Combination Treatment with Aminoglycosides and Mdm2 Inhibitors - Zhang, Meiqiongzi; Heldin, Angelos; Palomar-Siles, Mireia; Öhlin, Susanne; Bykov, Vladimir J. N.; Wiman, Klas G. (Frontiers in Oncology, 2018)
The tumor suppressor gene TP53 is inactivated by mutation in a large fraction of human tumors. Around 10% of TP53 mutations are nonsense mutations that lead to premature termination of translation and expression of truncated unstable and non-functional p53 protein. Aminoglycosides G418 (geneticin) and gentamicin have been shown to induce translational readthrough and expression of full-length p53. However, aminoglycosides have severe side effects that limit their clinical use. Here we show that combination treatment with a proteasome inhibitor or compounds that disrupt p53-Mdm2 binding can synergistically enhance levels of full-length p53 upon aminoglycoside-induced readthrough of R213X nonsense mutant p53. Full-length p53 expressed upon combination treatment is functionally active as assessed by upregulation of p53 target genes, suppression of cell growth, and induction of cell death. Thus, our results demonstrate that combination treatment with aminoglycosides and compounds that inhibit p53 degradation is synergistic and can provide significantly improved efficacy of readthrough as compared to aminoglycosides alone. This may have implications for future cancer therapy based on reactivation of nonsense mutant TP53.